2011
DOI: 10.1227/neu.0b013e3181fd860e
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgery for Previously Coiled Aneurysms: Experience With 81 Patients

Abstract: Complete microsurgical occlusion of the residual aneurysm is possible. However, in large or giant aneurysms direct microsurgery is a challenging high-risk procedure, and we recommend that these patients be referred to a dedicated neurovascular center to minimize surgical complications. Even in experienced hands, use of different bypass procedures may be the best option for demanding growing lesions, especially those in the posterior circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
0
48
1
Order By: Relevance
“…The feasibility of this procedure depends on several factors, including the time interval between the coiling procedure and microsurgical clipping, the position of the coils within the aneurysm, and the space available at the base of the aneurysm for clip placement. 1,21,27 Technical difficulties attributed to the coils present in the aneurysmal sac and neck are frequently encountered, making it difficult to properly clip the aneurysm and sometimes requiring removal of such coils. 9,11,25 The removal of coils for clip placement carries high morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The feasibility of this procedure depends on several factors, including the time interval between the coiling procedure and microsurgical clipping, the position of the coils within the aneurysm, and the space available at the base of the aneurysm for clip placement. 1,21,27 Technical difficulties attributed to the coils present in the aneurysmal sac and neck are frequently encountered, making it difficult to properly clip the aneurysm and sometimes requiring removal of such coils. 9,11,25 The removal of coils for clip placement carries high morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study that included 82 previously coiled aneurysms, Romani et al reported a similar rate (94%) of complete occlusion after surgical clipping. 21 Waldron et al reported that 32 of 33 (97%) previously coiled aneurysms were completely occluded without residual filling after microsurgical clipping. 27 Other smaller studies reported occlusion rates ranging from 83% to 100%.…”
Section: 21mentioning
confidence: 99%
See 3 more Smart Citations